The Influence Of Academic Leadership Styles On The Quality Of Higher Education In Indonesia - Abdul Wahid; Ahmad (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study investigates the influence of academic leadership styles on the quality of higher education in Indonesia, focusing on permanent lecturers in public and private universities under the Ministry of Education in South Sulawesi. Using a quantitative explanatory approach and survey method, data were collected from 120 respondents and analyzed through Structural Equation Modeling (SEM) using SmartPLS. The study examines three leadership styles—transformational, transactional, and distributed—and their impact on teaching quality, institutional governance, student outcomes, and academic services. The findings reveal that all three leadership styles positively affect higher education quality, with transformational leadership having the most significant impact, followed by distributed and transactional styles. These results underscore the importance of visionary and participative leadership in improving institutional performance, particularly in regional universities facing resource and structural limitations. The study contributes theoretically by validating leadership models in a non-Western context and practically by offering insights for leadership development policies. It highlights the need for adaptive leadership strategies tailored to local academic cultures and institutional dynamics to enhance educational quality in Indonesian higher education.